OBJEKTIVITAS PENILAIAN DIRI DALAM MATA KULIAH PENDIDIKAN MULTIKULTURALISME PADA MAHASISWA SEMESTER V STAI YAPIS TAKALAR TAHUN 2022 - Muthmainna, Alifah (STAI YAPIS Takalar, 2023)
Self-assessment is one of the assessment techniques recommended in the 2013 curriculum. In accordance with the mandate of the 2013 curriculum which aims to prepare Indonesian people to have the ability to live as individuals and citizens who are faithful, productive, creative, innovative and affective and able to contribute to social life, nation, state, and world civilization, it is necessary to pay attention to the formation of attitudes that can be done through self-assessment. With the hope that students are able to assess and understand themselves for what is needed and how to meet these needs. Self-assessment is difficult to do, because in general it is difficult for humans to assess and measure themselves. Self-assessment objectively can shape the character of students to be able to tell the truth and believe in themselves and others. However, an appropriate way is needed to measure the objectivity of self-assessment. Learning cultural multiculturalism education has different characteristics from other learning, not only in terms of knowledge and skills, but also focuses on attitudes, because it includes activities of appreciation, expression, and creation. Based on these characteristics, self-assessment which is a form of assessment contained in the 2013 curriculum is something that must be considered and carried out by the teacher to determine success in the learning process.